New baseband architectures using machine learning and deep learning in the presence of nonlinearities and dynamic environment - Reis, Ana Flávia dos (2024)
The forthcoming sixth generation (6G) of wireless communication systems is expected to enable a wide range of new applications in vehicular communication, which is accompanied by a diverse set of challenges and opportunities resulting from the demands of this cutting-edge technology. In particular, these challenges arise from dynamic channel conditions, including time-varying channels and nonlinearities induced by high-power amplifiers. In this complex context, wireless channel estimation emerges as an essential element in establishing reliable communication. Furthermore, the potential of machine learning and deep learning in the design of receiver architectures adapted to vehicular communication networks is evident, given their capabilities to harness vast datasets, model complex channel conditions, and optimize receiver performance. Throughout the course of this research, we leveraged these potential tools to advance the state-of-the-art in receiver design for vehicular communication networks. In this manner, we delved into the characteristics of wireless channel estimation and the mitigation of nonlinear distortions, recognizing these as significant factors in the communication system performance. To this end, we propose new methods and flexible receivers, based on hybrid approaches that combine mathematical models and machine learning techniques, taking advantage of the unique characteristics of the vehicular channel to favor accurate estimation. Our analysis covers both conventional wireless communications waveform and a promising 6G waveform, targeting the comprehensiveness of our approach. The results of the proposed approaches are promising, characterized by substantial enhancements in performance and noteworthy reductions in system complexity. These findings hold the potential for real-world applications, marking a step toward the future in the domain of vehicular communication networks.